Preparation method of boron-doped porous carbon-loaded potassium monatomic solid hydrogen storage material

Through the combination of boron-doped porous carbon materials and potassium single-atom loading, the problems of high cost and easy structure collapse of solid hydrogen storage materials are solved, and efficient and stable hydrogen storage and release performance are achieved.

CN119191225AActive Publication Date: 2024-12-27XIAN TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411227868.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-27
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The existing solid hydrogen storage materials are costly, have short cycle life and are prone to performance degradation in industrial production. The structure of porous carbon materials is prone to collapse when they are loaded with single metal atoms, resulting in a decrease in hydrogen storage efficiency.

Method used

The preparation method of porous carbon-loaded potassium single-atom solid hydrogen storage material using boron doped porous carbon, through boric acid-polyethylene glycol solution impregnation and high-temperature carbonization treatment, combined with heat treatment of potassium chloride dispersion, ensure that the boron doping is uniformly distributed and maintained Porous structure, potassium single atom loading improves hydrogen adsorption capacity.

Benefits of technology

It achieves high specific surface area, stability and recycling, improves hydrogen storage capacity and efficiency, and the hydrogen adsorption amount reaches 4.71 wt%, significantly improving the hydrogen storage density and the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191225A_ABST
    Figure CN119191225A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a boron-doped porous carbon-loaded potassium monatomic solid hydrogen storage material, which comprises the following steps: dissolving boric acid in a polyethylene glycol solution, stirring at room temperature until the boric acid is completely dissolved, adding porous carbon, fully stirring, standing and soaking at room temperature, and drying in vacuum to obtain a boron-doped porous carbon primary product; placing the boron-doped porous carbon primary product in a tubular furnace, heating at 900 DEG C for 3 hours under the protection of N2 atmosphere, and naturally cooling to obtain a boron-doped porous carbon material; and dispersing potassium chloride and the boron-doped porous carbon material in deionized water to obtain a potassium chloride-boron-doped porous carbon precursor dispersion liquid, carrying out centrifugal treatment, and carrying out heat treatment in a vacuum oven to obtain the boron-doped porous carbon-loaded potassium monatomic solid hydrogen storage material. The solid hydrogen storage material has the advantages that the prepared solid hydrogen storage material shows excellent hydrogen adsorption and desorption performance, when the hydrogen pressure is 70 Pa, the hydrogen adsorption capacity reaches 4.71 wt%, and the hydrogen storage density is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a boron-doped porous carbon-loaded potassium single-atom solid hydrogen storage material, which is mainly used for solid hydrogen storage materials. Background Art

[0002] In the field of solid-state hydrogen storage, existing research mainly focuses on the development of hydrogen storage materials with high hydrogen storage capacity, excellent cycle stability and suitable for large-scale production. However, these materials still face several technical challenges that need to be solved in practical applications. First of all, the preparation process of most current solid-state hydrogen storage materials usually involves complex process steps and high production costs, which significantly limits their application in industrial production. In addition, many existing materials are prone to performance degradation during long-term cyclic use, thereby reducing the cycle life of the materials and the reliability of practical applications. This performance degradation is mainly due to the changes in the internal structure of the material during multiple hydrogen absorption and desorption processes, resulting in a gradual decrease in its hydrogen storage efficiency. Another significant technical difficulty is that during the carbonization or activation stage, certain heteroatoms will catalyze unnecessary reactions, making the carbon framework unstable and causing the porous structure to partially or completely collapse. This collapse may be due to the introduction of strain or defects in the carbon lattice, resulting in a significant reduction in surface area.

[0003] CN117088332A discloses "a nitrogen-doped graphene-loaded alkaline earth metal calcium single atom non-cracking chemical adsorption hydrogen storage material and its preparation method". The method comprises the following steps: fully mixing melamine and graphene, heating to 900°C in a tubular furnace under the protection of a nitrogen atmosphere, then heating at this temperature for 3 hours, and cooling naturally under the protection of a nitrogen atmosphere to obtain nitrogen-doped graphene; adding calcium nitrate and nitrogen-doped graphene to deionized water, stirring evenly at room temperature, making the nitrogen-doped graphene evenly dispersed in the mixed solution, standing at room temperature, removing the supernatant, retaining the precipitate, placing in a vacuum freeze drying box, and freeze-drying at -20°C to obtain a nitrogen-doped graphene-loaded single atom calcium material. The advantages are: the surface area of ​​graphene as a two-dimensional material is mainly the part exposed to the outside, which is convenient for direct loading of metal calcium single atoms. The prepared non-cracking chemical adsorption hydrogen storage material is a surface-induced chemical adsorption, having a medium adsorption strength between physical adsorption and chemical reaction, and can obtain a good hydrogen storage density. The disadvantage is that although the graphene substrate has a large theoretical specific surface area (>2000m 2 / g), but the surface energy of this two-dimensional material is very large. During the metal single atom loading process, stacking is likely to occur, which greatly reduces the theoretical specific surface area and causes a serious reduction in the number of adsorption sites. It is impossible to fully utilize the advantage of the high specific surface area of ​​the adsorption-type hydrogen storage material, and the hydrogen storage density is not ideal.

[0004] As a typical three-dimensional structural material, porous carbon material has shown great potential in hydrogen storage and metal single atom loading with its extremely high specific surface area and rich pore structure. However, compared with two-dimensional graphene carriers, although porous carbon has significant advantages in specific surface area, its practical application faces challenges. As a two-dimensional material, the exposed external specific surface area of ​​graphene allows metal single atoms to be directly loaded on its surface. This feature greatly simplifies the loading process and improves the hydrogen storage performance. The high specific surface area of ​​porous carbon mainly comes from its complex pore structure. Although the internal specific surface area formed inside these pores theoretically increases the contact area with the gas, it also increases the difficulty of loading. When metal single atoms are loaded into the porous carbon, they need to overcome the limitations of the pore structure on material transfer, which may lead to low loading efficiency and uneven distribution. In addition, the loading process is prone to cause pore blockage or excessive structural stress, which in turn causes the collapse of the porous structure, seriously damaging the overall performance and stability of the material. Therefore, the application of porous carbon in solid-state hydrogen storage materials is severely limited. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a potassium single atom solid hydrogen storage material loaded with boron-doped porous carbon. The solid hydrogen storage material uses three-dimensional porous carbon as a base material, has a stable structure, and the pores will not collapse due to the doping and loading of heteroatoms. It is simple, efficient, and low-cost, and can improve the hydrogen storage capacity and cycle stability of the material, and the hydrogen adsorption and desorption amounts are highly consistent.

[0006] The technical solution of the present invention is:

[0007] A boron-doped porous carbon-loaded potassium single atom solid hydrogen storage material, which is special in that: the solid hydrogen storage material is single-atom potassium loaded on a boron-doped porous carbon material, the boron content in the solid hydrogen storage material is 3.17at%, and the potassium atom content is 0.1at%.

[0008] A method for preparing a boron-doped porous carbon-supported potassium single-atom solid hydrogen storage material, the specific steps of which are as follows:

[0009] S1: Preparation of Boric Acid-Polyethylene Glycol Solution

[0010] Dissolve boric acid in the polyethylene glycol solution according to the mass volume ratio of boric acid to polyethylene glycol of 4:1 g / mL, and stir at room temperature until completely dissolved to obtain a boric acid-polyethylene glycol solution;

[0011] S2: Impregnation of porous carbon

[0012] The porous carbon was added to the boric acid-polyethylene glycol solution according to the mass ratio of porous carbon to boric acid (H3BO3) of 1:8, ensuring that the porous carbon was completely immersed in the boric acid-polyethylene glycol solution, and after sufficient stirring, it was allowed to stand and soak at room temperature for 6 hours to allow the boric acid to fully enter the porous carbon material, and then vacuum dried to remove the solvent polyethylene glycol to obtain a preliminary boron-doped porous carbon product;

[0013] S3: Preparation of Boron-doped Porous Carbon Materials by High-temperature Carbonization

[0014] The boron-doped porous carbon preliminary product was placed in a tube furnace, heated at 900°C for 3 h under N2 atmosphere protection conditions, and cooled naturally to obtain a boron-doped porous carbon material;

[0015] S4: Preparation of potassium chloride-boron doped porous carbon precursor dispersion

[0016] Potassium chloride (KCl) and boron-doped porous carbon material were mixed in a mass ratio of 7:10 and dispersed in deionized water, stirred evenly at room temperature to obtain a potassium chloride-boron-doped porous carbon precursor dispersion, and centrifuged.

[0017] A potassium chloride-boron doped porous carbon black slurry is obtained;

[0018] S5: Preparation of solid-state hydrogen storage materials based on alkali metal single-atom potassium supported by boron-doped three-dimensional porous carbon

[0019] The black slurry of potassium chloride-boron doped porous carbon was placed in a vacuum oven, heat treated at 300°C for 3 hours, and then cooled to room temperature to obtain boron-doped porous carbon-loaded potassium single atom solid hydrogen storage material.

[0020] Furthermore, the volume ratio of polyethylene glycol to water in the polyethylene glycol solution is 1:50.

[0021] Furthermore, the total mass concentration of potassium chloride (KCl) and boron-doped porous carbon material in the potassium chloride-boron-doped porous carbon precursor dispersion is 1.7%.

[0022] Furthermore, during the vacuum drying in step S2, the drying temperature is 80° C. and the drying time is 24 h.

[0023] Furthermore, before centrifugation, the mixture was allowed to settle for 3 h.

[0024] The present invention uses boric acid as a precursor and porous carbon as a main material, and obtains a boron-doped porous carbon material by immersing it in a solubilizing agent and carbonizing it at high temperature, and then adds an appropriate amount of potassium chloride dispersion to obtain a potassium single-atom solid hydrogen storage material supported by boron-doped porous carbon through stirring, centrifugation, and heat treatment. Its beneficial effects are:

[0025] 1) The heteroatom boron is doped into porous carbon by impregnation with polyethylene glycol (PEG), ensuring that the boron atoms are uniformly doped and do not aggregate and stack in the pores. PEG is easy to remove and does not introduce extra impurities. In addition, the doping of boron atoms adjusts the interface configuration of porous carbon, breaks the symmetry of the electron density at the active sites, increases the lattice spacing in the porous carbon, and helps single atoms with larger radii to diffuse and load in the pores.

[0026] 2) Using potassium single atom loading, potassium single atom radius is larger, it can adsorb more hydrogen molecules, so that the porous carbon material has better hydrogen storage performance; at the same time, potassium loading on boron-doped porous carbon has a very small electrostatic Coulomb force interacting with the pore wall of boron-doped porous carbon, that is, a lower diffusion energy barrier, which is conducive to the preparation of the material.

[0027] 3) When boron is doped in porous carbon, it is first dried to remove the solvent solubilizer and not introduce redundant impurities. At the same time, it can avoid excessive crystallization and structural damage of the high-temperature pyrolysis process material, maintain the high specific surface area and microscopic pore structure of the porous carbon, and improve the cyclic hydrogen absorption and desorption stability of the material; by adjusting the amount of potassium chloride added, sufficient hydrogen absorption active sites are ensured, while effectively preventing pore blockage, structural damage and material performance degradation. The solid hydrogen storage material prepared by the present invention has a high hydrogen absorption capacity of up to 2224m 2 g -1 The specific surface area provides a large number of active adsorption sites for the storage of hydrogen, effectively improving the hydrogen storage capacity and efficiency; at a liquid nitrogen temperature of 77K, the solid hydrogen storage material prepared by the present invention exhibits excellent hydrogen adsorption and desorption properties. When the hydrogen pressure is 70 Pa, the hydrogen adsorption amount reaches 4.71wt%, and the hydrogen storage density is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 These are scanning transmission electron microscope (STEM) images of the potassium single atom material supported by the boron-doped porous carbon of the present invention (corresponding to Example 1) at different resolutions (a. 100 nm; b. 50 nm; c. 10 nm);

[0029] Figure 2 It is a scanning transmission electron microscope (STEM) energy spectrum and element distribution diagram of the potassium single atom material supported by boron-doped porous carbon of the present invention (corresponding to Example 1);

[0030] Figure 3 These are scanning electron microscope (SEM) images of the potassium single atom material supported by the boron-doped porous carbon of the present invention (corresponding to Example 1) at different resolutions (a. 20 μm; b. 1 μm);

[0031] Figure 4is an energy dispersive X-ray spectrum (EDS) diagram of the potassium single atom material supported by boron-doped porous carbon according to the present invention (corresponding to Example 1);

[0032] Figure 5 The high-resolution X-ray photoelectron spectrum (a) and the high-resolution X-ray sub-spectrum (b) of the potassium single-atom material supported by the boron-doped porous carbon of the present invention (corresponding to Example 1);

[0033] Figure 6 is an X-ray diffraction pattern of the potassium single atom material supported by boron-doped porous carbon according to the present invention (corresponding to Example 1);

[0034] Figure 7 is a nitrogen adsorption-desorption isotherm graph of the potassium single-atom material supported by the boron-doped porous carbon of the present invention (corresponding to Example 1);

[0035] Figure 8 is a pore distribution diagram of the potassium single atom material supported by the boron-doped porous carbon of the present invention (corresponding to Example 1);

[0036] Fig. 9 It is a hydrogen adsorption-desorption isotherm curve at liquid nitrogen temperature of the boron-doped porous carbon-supported potassium single-atom material of the present invention (corresponding to Example 1). DETAILED DESCRIPTION

[0037] The porous carbon powders used in Example 1 and Comparative Examples 1 to 8 of the present invention are porous carbons from the same batch.

[0038] Example 1

[0039] S1: Preparation of polyethylene glycol solution

[0040] Mix 2 mL of polyethylene glycol (PEG) with 100 mL of deionized water and stir thoroughly to prepare a polyethylene glycol solution;

[0041] S2: Preparation of Boric Acid-Polyethylene Glycol Solution

[0042] Dissolve 8 g of boric acid (H3BO3) in the polyethylene glycol (PEG) solution of step S1, and stir at room temperature until completely dissolved to prepare a boric acid-polyethylene glycol solution;

[0043] S3: Impregnation of porous carbon

[0044] Add 1 g of porous carbon to the boric acid-polyethylene glycol solution of step S2, completely immerse the porous carbon material in the boric acid-polyethylene glycol solution, stir sufficiently, and allow to stand and soak at room temperature for 6 hours to allow the boric acid to fully enter the porous carbon material, thereby obtaining a boric acid-polyethylene glycol-porous carbon material mixed solution;

[0045] S4: Preparation of initial boron-doped porous carbon

[0046] The boric acid-polyethylene glycol-porous carbon material mixture was placed in a vacuum oven and vacuum dried at 80° C. for 24 h to obtain a preliminary boron-doped porous carbon product;

[0047] S5: Preparation of Boron-doped Porous Carbon Materials by High-temperature Carbonization

[0048] The boron-doped porous carbon preliminary product was placed in a porcelain boat, and heated to 900°C at a heating rate of 10°C / min in a tube furnace under N2 atmosphere protection conditions, and the heat treatment was maintained at this temperature for 3 hours, and then the tube furnace was cooled to room temperature to obtain a boron-doped porous carbon material;

[0049] S6: Preparation of potassium chloride-boron doped porous carbon precursor dispersion

[0050] Weigh 1 g of boron-doped porous carbon material into a beaker, pour 0.7 g of potassium chloride (KCl), add 100 mL of deionized water, and stir evenly at room temperature to obtain a potassium chloride-boron-doped porous carbon precursor dispersion;

[0051] S7: Centrifugation

[0052] The precursor dispersion of potassium chloride-boron doped porous carbon was allowed to stand for 3 hours to allow for sufficient reaction and precipitation, and then centrifuged in a centrifuge, with the centrifugal speed set at 10000 r / min and the centrifugal time set at 10 minutes. After centrifugation, the supernatant was removed, and the lower layer of precipitation was retained, and then washed with deionized water for 3 times to obtain a black slurry of potassium chloride-boron doped porous carbon;

[0053] S8: Preparation of solid-state hydrogen storage materials based on alkali metal single-atom potassium supported on boron-doped three-dimensional porous carbon

[0054] The black slurry of potassium chloride-boron doped porous carbon was placed in a vacuum oven, heat treated at 300°C for 3 hours, and then cooled to room temperature to obtain boron-doped porous carbon-loaded potassium single atom solid hydrogen storage material.

[0055] In the structural characterization of the boron-doped porous carbon-supported potassium single-atom solid hydrogen storage material prepared in Example 1, the scanning electron microscopy images at different magnifications are as follows: Figure 1 As shown by Figure 1 (a) Figure 1 (b) Figure 1 It can be observed in (c) that there are a large number of fine pore structures, indicating that doping with boron and loading potassium atoms does not significantly change the basic morphology and size distribution of carbon. The turbine layered nanostructure in 1(c) further reveals that the material synthesized by this method can provide abundant sites for hydrogen embedding in the carbon layer, which is beneficial to improve the hydrogen storage capacity of the carbon material; the scanning transmission electron microscope (STEM) energy spectrum and its element distribution diagram are shown in Figure 2 As shown, the presence of C, B, and K elements and their uniform distribution are clearly shown, proving that this preparation method has successfully introduced potassium atoms into the surface of boron-doped porous carbon materials; Figure 3 In the scanning electron microscope (SEM) images at different resolutions (a.20μm; b.1μm), it can be observed that the material has a blocky particle structure, the deep contrast is the pore structure of the porous carbon, and the shallow contrast is the porous carbon wall. In addition, part of the pore structure is filled with boron and potassium atoms, which causes the surface of the material to appear smooth in these areas. This may be due to the shrinkage or coverage of the pores caused by atomic filling. At the same time, some unsuccessfully doped single atoms can also be observed on the carbon wall. These isolated atoms failed to be evenly embedded in the carbon matrix, forming isolated points with high contrast in the STEM image; Figure 4 In the energy dispersive X-ray spectroscopy (EDS) diagram, it can be noticed that the boron and potassium atoms are evenly dispersed on the surface and pores of the porous carbon material. The distribution positions of boron and potassium in EDS are the same as those of porous carbon in EDS, indicating the successful doping of boron atoms and the successful loading of potassium atoms into porous carbon. It can be seen that the high-resolution X-ray photoelectron spectrum of alkali metal single atoms potassium loaded by boron-doped three-dimensional porous carbon Figure 5 (a) shows that boron and potassium atoms were successfully introduced into the porous carbon, with a relative content of (B: 3.17at%; K: 0.1at%). The main reason why the peak of potassium atoms is not clearly visible is that the potassium atom loading concentration is relatively low, which inhibits the migration and aggregation of potassium atoms in the material and prevents the formation of crystals, so no obvious characteristic peak of potassium atoms is observed. Figure 5 (b) It can be seen that two boron-containing compounds BCO2 and BC3 are mainly formed in the material (excluding the precursor H3BO3 residue); in the X-ray diffraction pattern Figure 6 In the figure, two flat and broad peaks can be observed, which means that the alkali metal single atom potassium supported by boron-doped three-dimensional porous carbon is a low-crystallinity material; there is nitrogen adsorption and desorption amount such as Figure 7 As shown by Figure 7 It can be seen that the material has a large specific surface area, up to 2224m 2 g -1 The specific surface area is reduced compared with that of porous carbon, indicating that the doped and loaded single atoms fill part of the pores of porous carbon, which is confirmed by the STEM image results. The pore distribution diagram of the hydrogen storage material obtained in Example 1 is shown in Figure 8 As shown, the pore distribution of 2-20 nanometers accounts for a relatively high proportion. Analysis shows that the material is mainly composed of a mesoporous structure, accompanied by a small amount of macroporous structure.

[0056] In the hydrogen storage performance test of the boron-doped three-dimensional porous carbon-supported alkali metal single-atom potassium material obtained in Example 1, the hydrogen adsorption-desorption isotherm curve at liquid nitrogen temperature is as follows: Fig. 9 As shown, when the hydrogen pressure is 70 Pa, the hydrogen adsorption and desorption amount reaches 4.71wt%. At the same time, the adsorption and desorption curves are basically overlapped, which further illustrates the excellent hydrogen desorption and desorption ability of the boron-doped three-dimensional porous carbon-supported alkali metal single-atom potassium material prepared by the present invention.

[0057] Comparative Example 1 Alkali metal potassium single atom solid hydrogen storage material supported by porous carbon

[0058] S1: Drying of porous carbon materials

[0059] 2 g of porous carbon was placed in a beaker and heat treated at 200 °C for 3 h to remove excess water and obtain a dried porous carbon material;

[0060] S2: Preparation of dispersion of potassium chloride and porous carbon

[0061] Weigh 1 g of the dried porous carbon material into a beaker, add 0.7 g of potassium chloride (KCl), add 100 mL of deionized water, and stir evenly at room temperature to obtain a potassium chloride-porous carbon dispersion;

[0062] S3: Centrifugation

[0063] The potassium chloride-porous carbon dispersion was allowed to stand for 3 hours to allow for sufficient reaction and precipitation, and then centrifuged in a centrifuge, with the centrifugal speed set at 10,000 r / min and the centrifugal time set at 10 minutes. After centrifugation, the supernatant was removed and the precipitate at the lower layer was retained to obtain a black slurry of potassium chloride and porous carbon;

[0064] S4: Preparation of porous carbon-supported potassium single-atom solid-state hydrogen storage materials

[0065] The black slurry mixed with potassium chloride and porous carbon was placed in a vacuum oven, heat treated at 300°C for 10 hours, and then cooled to room temperature to obtain a porous carbon-supported potassium single-atom solid-state hydrogen storage material.

[0066] In the hydrogen storage performance test of the porous carbon-supported potassium single atom solid hydrogen storage material obtained in Comparative Example 1, hydrogen adsorption-desorption was performed at liquid nitrogen temperature. When the hydrogen pressure was 70 Pa, the hydrogen adsorption and desorption amount was less than 3wt%, and the hydrogen storage performance was poor. The reason for this result is presumably that the absence of boron doping promotes the porous carbon to form a more porous structure, and the loading amount of potassium single atoms on the porous carbon carrier becomes lower.

[0067] Comparative Example 2 Different boron precursor solutions

[0068] Boric acid (H3BO3) was replaced by boron oxide (B2O3), and the other conditions were the same as those in Example 1 without any other changes. A solid hydrogen storage material of alkali metal potassium single atom supported by boron-doped three-dimensional porous carbon was prepared.

[0069] In the hydrogen storage performance test of the solid hydrogen storage material of alkali metal potassium single atom supported by boron doped three-dimensional porous carbon obtained in Comparative Example 2, hydrogen adsorption-desorption was carried out at liquid nitrogen temperature. When the hydrogen pressure was 70 Pa, the hydrogen adsorption-desorption amount was 4.13wt%. It can be inferred that the boric acid molecules are easier to penetrate into the pores of the porous carbon material due to their smaller size, thereby achieving uniform doping distribution. In contrast, boron oxide particles are difficult to penetrate into the fine pores in the porous carbon material due to their larger size, so they tend to agglomerate in larger pores, resulting in uneven doping process.

[0070] Comparative Example 3 Different solubilizers

[0071] S1: Preparation of acetone solution

[0072] Mix 8 mL of acetone (C3H6O) with 100 mL of deionized water and stir thoroughly to prepare an acetone solution;

[0073] S2: Preparation of boric acid-acetone solution

[0074] Dissolve 8 g of boric acid (H3BO3) in the acetone solution of step S1, and stir at room temperature until completely dissolved to prepare a boric acid-acetone solution;

[0075] S3: Impregnation of porous carbon

[0076] Add 1 g of porous carbon to the boric acid-acetone solution of step S2, completely immerse the porous carbon material in the boric acid-acetone solution, stir sufficiently, and allow to stand and soak at room temperature for 6 hours to allow the boric acid to fully enter the porous carbon material, thereby obtaining a boric acid-acetone-porous carbon material mixed solution;

[0077] S4-S8: Subsequent steps are the same as those in Example 1, without other changes.

[0078] In the hydrogen storage performance test of the solid hydrogen storage material of alkali metal potassium single atom supported by boron-doped three-dimensional porous carbon obtained in Comparative Example 3, hydrogen adsorption-desorption was carried out at liquid nitrogen temperature, and when the hydrogen pressure was 70 Pa, the hydrogen adsorption-desorption amount was 3.87wt%. This result shows that the solubilizer selected in Example 1 of the present application, polyethylene glycol, has a unique effect in promoting the loading of potassium single atoms in the porous carbon structure.

[0079] Comparative Example 4 Different Boron Doping Processes

[0080] S1: Preparation of Boric Acid Solution

[0081] Dissolve 8 g of boric acid (H3BO3) in 100 mL of deionized water and stir until completely dissolved to obtain a boric acid solution;

[0082] S2: Mixing porous carbon with boric acid solution

[0083] Add 1 g of porous carbon to the boric acid solution prepared above and stir thoroughly at room temperature to allow the boric acid to fully contact the porous carbon;

[0084] S3: Vacuum drying

[0085] The mixed porous carbon and boric acid solution were placed in a vacuum oven and vacuum dried at 80° C. for 24 h to remove moisture and excess boric acid, thereby obtaining a preliminary boron-doped porous carbon product;

[0086] S4: Preparation of Boron-doped Porous Carbon Materials by High-temperature Carbonization

[0087] The boron-doped porous carbon preliminary product was placed in a porcelain boat, and heated to 900°C at a heating rate of 10°C / min in a tube furnace under N2 atmosphere protection conditions, and the heat treatment was maintained at this temperature for 3 hours, and then the tube furnace was cooled to room temperature to obtain a boron-doped porous carbon material;

[0088] S5: Preparation of potassium chloride-boron doped porous carbon precursor dispersion

[0089] Weigh 1 g of boron-doped porous carbon material into a beaker, pour 1 g of potassium chloride (KCl), add 100 mL of deionized water, and stir evenly at room temperature to obtain a potassium chloride-boron-doped porous carbon precursor dispersion;

[0090] S6: Centrifugation

[0091] The precursor dispersion of potassium chloride-boron doped porous carbon was allowed to stand for 3 hours to allow for sufficient reaction and precipitation, and then centrifuged in a centrifuge, with the centrifugal speed set at 10000 r / min and the centrifugal time set at 10 minutes. After centrifugation, the supernatant was removed, and the lower layer of precipitation was retained, and then washed with deionized water for 3 times to obtain a black slurry of potassium chloride-boron doped porous carbon;

[0092] S7: Preparation of solid-state hydrogen storage materials based on alkali metal single-atom potassium supported by boron-doped three-dimensional porous carbon

[0093] The black slurry of potassium chloride-boron doped porous carbon was placed in a vacuum oven, heat treated at 300°C for 3 hours, and then cooled to room temperature to obtain boron-doped porous carbon-loaded potassium single atom solid hydrogen storage material.

[0094] In the hydrogen storage performance test of the solid hydrogen storage material of alkali metal potassium single atom supported by boron-doped three-dimensional porous carbon obtained in Comparative Example 4, hydrogen adsorption-desorption was carried out at liquid nitrogen temperature. When the hydrogen pressure was 70 Pa, the hydrogen adsorption and desorption amount was 3.71wt%, which was less than that of the material obtained by doping with boron through the impregnation process. This result proves the importance of the solubilizer impregnation step. Doping can more effectively distribute the dopant evenly into the pore structure of the porous carbon material through the diffusion effect of the solubilizer. This uniform distribution helps to improve the uniformity of the dopant in the material, thereby optimizing the overall performance of the material.

[0095] Comparative Examples 5-8 Different Addition Amounts of Potassium Chloride

[0096] Comparative Example 5

[0097] The amount of potassium chloride added was 0.1 g, and the rest was the same as in Example 1.

[0098] Comparative Example 6

[0099] The amount of potassium chloride added was 0.3 g, and the rest was the same as in Example 1.

[0100] Comparative Example 7

[0101] The amount of potassium chloride added was 0.5 g, and the rest was the same as in Example 1.

[0102] Comparative Example 8

[0103] The amount of potassium chloride added was 1 g, and the rest was the same as in Example 1.

[0104] Four groups of different potassium chloride addition amounts are set, and the other preparation conditions are the same as those in Example 1. Preparation Method of Alkali Metal Single Atom Potassium Supported by Boron-Doped Three-Dimensional Porous Carbon The parameters of Comparative Examples 5 to 8 are shown in Table 1 below:

[0105] Table 1 is the parameters of the preparation method of alkali metal single atom potassium supported by boron doped three-dimensional porous carbon in comparative examples 5 to 8

[0106]

[0107] The samples prepared in Comparative Examples 5 to 8 were subjected to nitrogen adsorption-desorption tests under isothermal conditions and hydrogen storage performance tests under liquid nitrogen (77K) temperature and 70 Pa hydrogen pressure. The specific surface areas obtained from the tests of Comparative Examples 5 to 8 and the hydrogen adsorption and desorption amounts under 77K temperature and 70 Pa hydrogen pressure are shown in Table 2 below:

[0108] Table 2 is the detection data of alkali metal single atom potassium supported by boron-doped three-dimensional porous carbon in comparative examples 5 to 8

[0109]

[0110] 1. Performance Analysis of Example 1 of the Present Invention and Comparative Examples 1 to 8 of Parallel Tests

[0111] From the fact that the performance of the solid hydrogen storage material loaded with only potassium units in Comparative Example 1 is not as good as that of the material obtained in Example 1, it can be seen that the doping of boron atoms is indispensable and is crucial to the improvement of the hydrogen storage performance of porous carbon materials; Comparative Examples 2 and 3 respectively illustrate that the selection of boron doping liquid and solubilizer is unique; Comparative Example 4 shows that the impregnation process is an indispensable step to promote the uniform doping of boron into porous carbon materials; from the performance test data shown in Table 2, compared with the test results in Example 1, a small amount or an excessive amount of potassium chloride additives has no promoting effect on the specific surface area of ​​the material and the adsorption and desorption of hydrogen. Among them, the specific surface area data in Table 2 show that the addition of too little or too much potassium chloride will slightly reduce the specific surface area of ​​the material, indicating that the amount of 0.7g of potassium chloride in Example 1 is most suitable for forming an ideal pore distribution and achieving a higher degree of potassium doping, thereby enhancing the hydrogen storage performance. It further shows that the effect of potassium chloride on the porosity and specific surface area of ​​the material is not linear, and the amount of potassium chloride in Example 1 of the present invention can enhance these characteristics without causing negative effects. When the amount of potassium chloride is too much, the excess residual potassium chloride cannot be completely dissolved or evenly distributed during the carbonization process and accumulates in the pores, thereby reducing the effective surface area available for adsorption and storage, affecting the hydrogen storage performance of the material. A lower amount of potassium chloride cannot provide enough potassium to form the same porosity or potassium content, resulting in poor hydrogen storage effect of the material.

[0112] II. Effect Analysis of the Boron-doped Porous Carbon-supported Potassium Single Atom Solid Hydrogen Storage Material of Example 1 of the Present Invention

[0113] Through the structural characterization and performance testing of the boron-doped three-dimensional porous carbon-loaded alkali metal single-atom potassium material prepared in Example 1, some important conclusions were drawn. From the SEM and STEM image analysis, a large number of fine pore structures are shown on the surface of the material, indicating that the doping of boron and the loading of potassium single atoms have not significantly changed the basic morphology of the porous carbon material. Especially under the manifestation of turbine layered nanostructures, this material can provide abundant active sites for the adsorption of hydrogen, significantly improving its hydrogen storage capacity. The STEM energy spectrum and its element distribution map further confirmed the uniform distribution of C, B, and K elements in the material, indicating that the method has successfully achieved the introduction of potassium single atoms on the surface of boron-doped porous carbon. At the same time, the results of EDS and XPS show that boron mainly exists in the form of BCO2 and BC3 compounds, and the low crystallinity single-atom doping / loading characteristics of the material are confirmed by XRD. In the nitrogen adsorption and desorption test, the material exhibited a high crystallinity of up to 2224m 2 / g specific surface area, although it is lower than that of pure porous carbon, this shows that the doping and potassium single atom loading partially fill the pores of porous carbon. The pore size distribution diagram shows that the material is mainly mesoporous structure, and the pore size of 2-20 nanometers accounts for a relatively high proportion. This pore structure helps to enhance the adsorption performance of hydrogen. The hydrogen storage performance test results show that at liquid nitrogen temperature, when the hydrogen pressure reaches 70 Pa, the hydrogen adsorption and desorption amount of the material reaches 4.71wt%. And the adsorption and desorption curves basically coincide, further proving that the material has excellent hydrogen storage and release capabilities. These results show that the boron-doped three-dimensional porous carbon-loaded potassium single atom solid hydrogen storage material of the present invention not only has a reasonable structural design, but also shows significant superiority in hydrogen storage performance, which provides possibilities for future applications in large-scale hydrogen storage.

Claims

1. A boron-doped porous carbon-supported potassium single-atom solid hydrogen storage material, characterized in that: The solid hydrogen storage material is a single-atom potassium loaded on a boron-doped porous carbon material, and the boron content in the solid hydrogen storage material is 3.17 at%, and the potassium atom content is 0.1 at%.

2. The method for preparing the boron-doped porous carbon-supported potassium single-atom solid hydrogen storage material according to claim 1, characterized in that: The specific steps are as follows: S1: Preparation of Boric Acid-Polyethylene Glycol Solution Dissolve boric acid in the polyethylene glycol solution according to the mass volume ratio of boric acid to polyethylene glycol of 4:1 g / mL, and stir at room temperature until completely dissolved to obtain a boric acid-polyethylene glycol solution; S2: Impregnation of porous carbon The porous carbon was added to the boric acid-polyethylene glycol solution according to the mass ratio of porous carbon to boric acid (H3BO3) of 1:8, ensuring that the porous carbon was completely immersed in the boric acid-polyethylene glycol solution, and after sufficient stirring, it was allowed to stand and soak at room temperature for 6 hours to allow the boric acid to fully enter the porous carbon material, and then vacuum dried to remove the solvent polyethylene glycol to obtain a preliminary boron-doped porous carbon product; S3: Preparation of Boron-doped Porous Carbon Materials by High-temperature Carbonization The boron-doped porous carbon preliminary product was placed in a tube furnace, heated at 900°C for 3 h under N2 atmosphere protection conditions, and cooled naturally to obtain a boron-doped porous carbon material; S4: Preparation of potassium chloride-boron doped porous carbon precursor dispersion Potassium chloride (KCl) and boron-doped porous carbon material were mixed in a mass ratio of 7:10 and dispersed in deionized water, stirred evenly at room temperature to obtain a potassium chloride-boron-doped porous carbon precursor dispersion, and centrifuged. A potassium chloride-boron doped porous carbon black slurry is obtained; S5: Preparation of solid-state hydrogen storage materials based on alkali metal single-atom potassium supported by boron-doped three-dimensional porous carbon The black slurry of potassium chloride-boron doped porous carbon was placed in a vacuum oven, heat treated at 300°C for 3 hours, and then cooled to room temperature to obtain boron-doped porous carbon-loaded potassium single atom solid hydrogen storage material.

3. The method for preparing the boron-doped porous carbon-supported potassium single-atom solid hydrogen storage material according to claim 2, characterized in that: The volume ratio of polyethylene glycol to water in the polyethylene glycol solution is 1:

50.

4. The method for preparing the boron-doped porous carbon-supported potassium single-atom solid hydrogen storage material according to claim 2, characterized in that The total mass concentration of potassium chloride (KCl) and boron-doped porous carbon material in the potassium chloride-boron-doped porous carbon precursor dispersion is 1.7%.

5. The method for preparing the boron-doped porous carbon-supported potassium single-atom solid hydrogen storage material according to claim 2, characterized in that During vacuum drying in step S2, the drying temperature is 80° C. and the drying time is 24 h.

6. The method for preparing the boron-doped porous carbon-supported potassium single-atom solid hydrogen storage material according to claim 2, characterized in that Before centrifugation, the solution was allowed to settle for 3 h.

Citation Information

Patent Citations

  • Method for preparing boron-doped porous carbon spheres

    CN107346821A

  • Preparation method of heteroatom doped porous carbon supported monatomic catalyst

    CN115282999A

  • Nitrogen-doped graphene-loaded light metal lithium monatomic hydrogen storage material and preparation method thereof

    CN116854031A

  • Porous carbon and method for preparing the same

    KR1020150134170A

  • Nitrogen and Metal doped Porous Carbon Materials and Method of Manufacturing the Same

    KR1020160110649A